High Order Learning Process in Core School of Anggrek Cluster in Candisari District Semarang - Mubarokah, Isna Rizki; Mulyono, Sungkowo Edy; Syamwil, Rodia (Universitas Negeri Semarang, 2019)
The 2013 curriculum and the implementation of HOTS are urgently needed to create future generations, not only characterized, productive, creative, and innovative but also who understand the national identity and create children who are superior and able to compete in the international world. The scientific approach can be a tool that teachers use to be able to carry out learning that can lead to high-level thinking learning for kindergarten, this is also contained in the 2013 curriculum. This study aims to analyze the high order thinking of kindergarten in the core orchid cluster school in Candisari District, Semarang. The research is a qualitative research. Which concern in the learning process carried out in class by the teacher to the child both from the strategies used and the communication that the teacher did while in the learning process. The result from the study is that Taman Belia Candi as the core school of Anggrek cluster has already used high-order thinking learning. This can be seen from the lesson plans used and also the learning process carried out. The conclusion that can be drawn from this research is that the high-level learning process for early-aged children has been carried out in the Anggrek cluster core school, Candisari District, Semarang, this can be seen from the scientific approach use in the learning process in the classroom.